INDUKSI PEMBUNGAAN TANAMAN VANILI SECARA MEKANIS DENGAN PEMANGKASAN KIMIA MENGGUNAKAN PACLOBUTRAZOL DAN APLIKASI TRICHODERMA - S. Suryanti; R. Widyasaputra; H.G. Mawandha; A. Himawan (Buletin Udayana Mengabdi, 2024)
Vanilla (Vanilla planifolia Andrews) is a plantation commodity with high economic value and has long been developed by the Ayem farmer group in Sinogo Village through the Mbajing Learning House (Rube). In their cultivation, vanilla farmers in Sinogo Village have problems in making plants stressed (stressing periods) so that plants can not bloom. Therefore, community service activities are carried out regarding the induction of vanilla flowering. With this PKM activity, it is hoped that farmers can understand and apply the correct vanilla cultivation techniques and apply several flowering induction techniques. This is done because from hasil survey conducted shows that 100% of vanilla farmers of Sinogo Village in vanilla cultivation still use local varieties. Sinogo farmers were not yet familiar with the high-yielding varieties of vanilla produced by the Ministry of Agriculture. The planting medium used soil, cocopit and manure. The flowering induction technique that has been carried out was only mechanically by trimming the tendrils so that when the rainfall is high, the flower stressing does not work. There were PKM activities carried out counseling on superior varieties of vanilla, correct vanilla cultivation techniques and several flowering induction techniques, namely mechanically by means of prunning, chemically using paclobutrazol and biologically using the fungus Trichoderma. Keywords : Induction, Flowering, Vanilla, Cutting, Paclobutrazol, Trichoderma